Diminished trophoblast differentiation in early onset preeclampsia. (24th March 2022) - Natenzon, Anna; McFadden, Patrick; DaSilva-Arnold, Sonia C.; Zamudio, Stacy; Illsley, Nicholas P.
Abstract: The mechanism by which human cytotrophoblast cells (CTB) differentiate into extravillous trophoblast cells (EVT) is an epithelial-mesenchymal transition (EMT). Polarized CTB, anchored in an epithelial layer, are transformed into motile, non-polar EVT which invade the uterus. Our previous research has shown that over gestation, invasive first trimester EVT are converted to a non-invasive phenotype showing a reduced degree of EMT. We hypothesized that in an under-invasion pathology, such as early onset preeclampsia, third trimester EVT would display a less advanced EMT profile than controls. The goal of this study was to determine whether expression of EMT-associated genes in the EVT of early onset preeclamptics shows a less mesenchymal, more epithelial phenotype compared to control pregnancies. Measures of preeclamptic CTB and EVT gene expression, using highly purified cells from third trimester, early onset preeclamptics and gestational-age matched controls, showed clear evidence of a phenotypic pattern characteristic of an EMT. Comparison of preeclamptic EVT to gestational-age matched, control EVT demonstrated multiple changes in gene expression, including changes in well-known EMT gene markers, indicative of a more limited EMT. These changes are not explained by differences in the preeclamptic CTB precursors. In this first study of purified third trimester EVT, we show that the pattern of gene expression corresponding to EMT-associated differentiation is diminished in early onset preeclampsia. This provides a mechanistic framework for many of the molecular changes observed in preeclampsia and presents an opportunity for detailed studies of the pathways regulating the aberrant EMT and for potential biomarkers of the process. Graphical abstract: Image 1 Highlights: Comparison of CTB and EVT gene expression in preeclamptics showed evidence of an EMT. Preeclamptic EVT show a diminished EMT, consistent with the reduced invasiveness. The reduced degree of EMT in preeclampsia was associated with the differentiation process.